Seasonal Variations of Impedance in the Ionospheric Plasma - Unal, Ibrahim; Karatay, Secil; Yesil, Ali; Hancerliogullari, Aybaba (Gazi Univ, 2020)
The ionosphere is an ionized layer that extends between 50 km and 1000 km altitudes in the atmosphere. It plays an important role in atmospheric electricity. The ionosphere has the number of electrically charged particles and thus, it affects the propagation of the radio waves. In this study, magnitudes of impedance for different seasons and different geomagnetic activity periods in the ionospheric plasma are calculated using the real geometry of Earth. It is observed that the impedance of the ionospheric plasma in all directions generally has high values for all seasons. The diagonal components of the tensor of the impedance are greater than the other components. It is also observed that the ionospheric plasma, generally, has weak conductivity in all directions and seasons. Impedance varies inversely with electron density. Hence, geomagnetic activity periods which lead to an increase in electron density decreases the impedance. It is observed that the ionospheric plasma has a reactive character in the geographic coordinates where the study was performed. The ionosphere displays a dielectric structure.
Keywords: Impedance; electromagnetics; plasma applications; ionosphere; magnetosphere